DEVELOPING STUDENT CHARACTER: A Case Study of KTSP Islamic Education Subject - Mariatul Hikmah (Madania: Jurnal Ilmu-Ilmu Keislaman, 2011)
A good curriculum should produce a good educational process and good educational product. Also, a bad curriculum will create a bad implementation. It means that a curriculum has become a starting point. Referring to national standard which becomes the reference of KTSP development, character building has included in teaching material which should be mastered and implemented by learners in their everyday life. The learning material related to norms or values should be developed with everyday life context. As a result, teaching character building is not only in cognitive level but it should touch with real experiences of the learners in the society